Le sanctuaire rural de Bennecourt (Yvelines) Du temple celtique au temple gallo-romain - Bourgeois, Luc (Documents d'archéologie française, 1999)
Established where the Île-de-France region meets Normandy, the rural sanctuary in Bennecourt was occupied from the 2nd century BC to the 4th century AD. Excavations camed out from 1982 to 1988 have revealed the gradual progression from a Gallic enclosure housing a small building on pillars, to a vast peribolus surrounding three stone temples A set of secondary features and an abundant collection of artefacts (close to 25,000 objects and fragments) have been preserved, making this a reference site for northern Gaul. After a detailed study of the structures and the artefacts, the author Luc Bourgeois presents an overview that suggests some directions tor research on Celtic cult structures and their evolution in Gallo-Roman era : a nuanced approach to architectural filiation, aspects of sacrificial cooking and the place occupled by this type of site in a regional framework